Assistência à saúde bucal da gestante no estado do Maranhão: desafios da gestão - PESSOA, Inês Barros (2022)
The objective of this research was to analyze the organization of the oral health care service for pregnant women in the state of Maranhão. This research is part of the project Oral health care for pregnant women in the state of Maranhão: management challenges This is an ecological, descriptive and exploratory study, with primary and secondary data from the municipalities of the state. The primary data were collected through a form sent electronically to all those responsible for the municipal coordination of oral health actions in Maranhão, in the period from May to July 2022, totaling 100 municipalities respondents. The variables collected through this instrument were: existence of the position of oral health coordinator; training of the oral health coordinator; sector responsible for the organization of actions; types of dental actions and services offered to pregnant women in Primary Health Care; existence of protocols of care for the oral health of pregnant women. The information was entered into Microsoft Excel® software and exported to Stata® 12.0 and allowed the mapping of the scenario of oral health care in the state. Secondary data were collected from the Primary Health Care Information System (SISAB) and IBGE, totaling 217 municipalities, the variables collected were: proportion of pregnant women with dental care performed, proportion of coverage and number of Oral Health teams and Family Health Strategy and HDI. The analyzed municipalities represent 1138 oral health teams (65.78%), of which 1059 (61.21%) were indicated by the respondent manager that perform dental prenatal care. It was identified that the oral health coordinators of the municipalities have a mean age of 33.79 years, being predominantly male 62% (n=62). Of these, only 16% (n=16) have a post-graduation in collective health. Regarding oral health care, only 32% (n=32) stated that there are clinical protocol determinations for dental care to pregnant women in PHC, 28% (n=28) of municipalities reported that they have no record of this flow and 46% (n=46) do it through a physical document. It was also observed that the historical series shows that the proportion of pregnant women with dental care performed in Maranhão had a slight evolution from 2018 to the first four months of 2021, but there was a more expressive performance in the last two quarters of 2021. Furthermore, there was no statistical correlation between the proportion of pregnant women with dental care performed and IDH-M, coverage of eSB, and population size of the municipalities. The findings show that there was an increase in the proportion of dental consultations during prenatal care in the years analyzed. The oral health coordinators in these municipalities have little experience in performing their function. It was also observed that there are no standardized clinical protocols for dental care to pregnant women, causing professionals to act without guidelines for clinical conducts.